Reactor Design and Optimization of α-Amino Ester Hydrolase- Catalyzed Synthesis of Cephalexin - Lagerman, Colton E.; Grover, Martha A.; Rousseau, Ronald. W.; Bommarius, Andreas S. (Frontiers in Bioengineering and Biotechnology, 2022)
Pharmaceutical production quality has recently been a focus for improvement through incorporation of end-to-end continuous processing. Enzymatic ß-lactam antibiotic synthesis has been one focus for continuous manufacturing, and α-amino ester hydrolases (AEHs) are currently being explored for use in the synthesis of cephalexin due to their high reactivity and selectivity. In this study, several reactors were simulated to determine how reactor type and configuration impacts reactant conversion, fractional yield toward cephalexin, and volumetric productivity for AEH-catalyzed cephalexin synthesis. The primary reactor configurations studied are single reactors including a continuous stirred-tank reactor (CSTR) and plug flow reactor (PFR) as well as two CSTRS and a CSTR + PFR in series. Substrate concentrations fed to the reactors as well as enzyme concentration in the reactor were varied. The presence of substrate inhibition was found to have a negative impact on all reactor configurations studied. No reactor configuration simultaneously allowed high substrate conversion, high fractional yield, and high productivity; however, a single PFR was found to enable the highest substrate conversion with higher fractional yields than all other reactor configurations, by minimizing substrate inhibition. Finally, to further demonstrate the impact of substrate inhibition, an AEH engineered to improve substrate inhibition was simulated and Pareto optimal fronts for a CSTR catalyzed with the current AEH were compared to Pareto fronts for the improved AEH. Overall, reduced substrate inhibition would allow for high substrate conversion, fractional yield, and productivity with only a single CSTR.